Tar-free and benzo[a]pyrene-free hydrothermal liquefaction of bamboo and antibacterial property of recovered vinegar - Yamashiro, Keisaku; Ariffin, Hidayah; Nishida, Haruo (Chemical Society of Japan, 2015)
Bamboo, which was treated using superheated steam controlled at a low temperature range, gave tar-free and benzo[a]pyrene-free vinegar. The vinegar’s selective antibacterial activity against Staphylococcus aureus concerned with the atopic dermatitis and Bacillus cereus causing food poisoning in humans was confirmed, while no effect was found against Escherichia coli and Bacillus subtilis as being indigenous bacteria in natural environments.